Analysis of Community and Security Forces Collaboration through Socialization of Organizational Culture in the Implementation of the PILKADA 2024 Bekasi City in Margajaya Village, South Bekasi District, Bekasi City - Hidayanti, Mardiana Tri; Agus Cholik; Salsya Nuri Wafdah Sauqi; Alfiyani Dewi Rakadita (International Publisher, 2024)
Regional Head Elections (Pilkada) are a crucial component in Indonesia's democratic system that directly influences regional development, including in Bekasi. This study examines how organizational culture plays a role in optimizing interactions between security officers and the community to create supportive conditions during the Pilkada. The study was conducted in Margajaya Village, South Bekasi, using qualitative descriptive methodology. Data collection was conducted through a series of in-depth interviews, direct observation, documentation, and focus group discussions (FGD). The research findings indicate several obstacles in socializing organizational culture , including lack of community knowledge and obstacles in communication. The main challenges include efforts to build trust between officers and residents, and maintaining the professional attitude of officers in the field. Several solutions proposed include community-based socialization, improving officer communication skills, using information technology, and forming a work team.